Formulation and Evaluation of Controlled Release Maintenance Dose Loaded Niosomes of Anti-Hypertensive Drug (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
The present study was aimed to formulate, comparatively evaluate and optimize multiple lipid drug carriers of valsartan for oral controlled release to overcome the problems associated with the drug such as bioavailability, to reduce the dosage regimen, half life and to determine the appropriateness of niosomal formulation as a drug carrier. Ether injection method was chosen for the formulation of physically and chemically stable niosomes of valsartan. The formulation and process parameters were optimized by manufacturing placebo niosomes. Than drug loaded niosome was prepared by varying the concentration of span 60. The prepared nine formulations were evaluated for various parameters. Placebo niosomes were evaluated for appearance, odour, texture, creaming volume, pH and changes after 15 days. The medicated nine formulations were evaluated for organoleptic properties (appearance/color, odour), pH, total drug content, entrapment efficiency, mean particle size and polydispersibility index, zeta potential and In-vitro drug release. All formulations were off-white in color, odourless, and fluid in nature. It was stable and did not show sedimentation. The pH was found to be in the range of 4.6-5.4. Drug content was found in the range of 89.13 to 99.52. The Entrapment efficiency was found in range of 79.05 to 98.24. The mean vesicle size of drug loaded niosomes of the different batches ranged between 2.52-3.42μm. The polydispersvity index was in the range of 0.325 to 0.420 which indicates a narrow vesicle size distribution. The values of zeta potential were in the range of -20.29 mV to -30.55 mV which indicates that niosome had sufficient charge and mobility to inhibit aggregation of vesicles. All the nine formulations shows constant drug release in controlled manner up to 24 h. Formulation V7 was considered to be the best formulation as the % drug content (99.52 ± 0.97), % entrapment efficiency (98.24 ± 1.50) and % drug release at the end of 24th h (98.55) were high for V7. The optimized formulation V7 showed higher degree of correlation coefficient (r2) 0.9805 which indicates process of constant drug release from dosage form. The present study concludes that the prepared niosome is a convenient and efficiency carrier for the delivery of antihypertensive drug. Besides this, it provided controlled delivery of drug.